New Drugs and Clinical Trials Rules, 2019: Towards Fast-track Accessibility of New Drugs to the Indian Population - Dubey, Akhilesh; Kotian, Bhasini; Shriram, Ravi Gundadka (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: To fulfil the objective of fast-tracking the accessibility of new drugs and promoting clinical research in India, the Union Ministry of Health and Family Welfare, India has notified the “New Drugs and Clinical trials Rules, 2019” on 25th March 2019. The prime objective of the new rule is to initiate unambiguous, foreseeable and effective regulations for the clinical trials in India. Drugs Controller General of India (DCGI) affirmed that the new rules would apply to all new drugs, investigational new drugs, bioequivalence and bioavailability study (BA/BE) and ethics committees. The new rules would replace part XA and schedule Y of drugs; however, the existing rules (Drugs and Cosmetics Act, 1940; Drug and Cosmetics Rules, 1945) and licenses, orders or directions will remain valid. Purpose: This brief review aims at presenting the key highlights of the “New Drugs and Clinical Trials Rules, 2019” of India. Methods: Literature review in existing and new clinical trials rules in India was conducted by referring the articles published in the indexed journals and official websites and compared. Conclusion: The clinical trials approval timeline has moved down to 30 days for the domestic trials and 90 days for the approval of global clinical trials. This faster approval timelines in the newly amended rules have enabled approval of more number of clinical trials and as a result, India may again turn out to be the preferred centre for conducting the trials.
Keywords: Clinical trials; New Drugs and Clinical trials Rules 2019; DCGI; India